Pengembangan Bahan Ajar Cerita Fantasi Berbantuan Wondershare Filmora Di Kelas VII SMP Muhammadiyah 12 Kota Binjai - Gading Hakim Alamsyah Daulay; Muharrina Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to develop teaching materials for fantasy stories in the form of videos with the help of the Wondershare Filmora application in class VII SMP. This research is development research (RnD) using the Borg and Gall research procedure, which has been simplified in stages and adapted to the needs and limitations of this study. The stages carried out in this study are a) Potential and Problems, b) Data Collection, c) Product Design, d) Validation, and e) Revision. The subject of this development research is to get the valid results of the product from the three validators, namely material expert validators, media experts, and Indonesian language subject teachers at SMP Muhammadiyah 12 Kota Binjai. Data collection techniques include interviews with subject teachers and questionnaires that will be conducted to find out the needs of students. The results of this study indicate that the products developed from this research, namely teaching materials for fantasy stories assisted by Wondershare Filmora in the form of videos, are included in very feasible/good qualifications with a value from material validators of 78.8% and media experts of 89.6% and subject teachers of 92.5%. An average value of 86.9% is obtained to conclude that the products in this study are very good/feasible for teachers' and students' learning use.